Response of various histological types of locally advanced rectal cancer to neoadjuvant multimodality therapy - Nadeem, Muhammad Sohaib; Ujala Ali; Khan, Amjad; Wajid, Imran; Riaz, Omer; Azeem, Muhammad Tariq (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the response of various histological types of locally advanced rectal cancer to neoadjuvant multimodality therapy. Method: The non-randomised, quasi-experimental retrospective cohort study was conducted at the Combined Military Hospital, Rawalpindi, Pakistan, and comprised data of patients treated between January 1, 2020, to September 30, 2021. The data retrieved related to histologically proven and locally advanced rectal cancer patients aged 18-70 years receiving neoadjuvant chemoradiotherapy. Radiotherapy dose was 45 gray to pelvis with a boost to gross tumour of 5.4 gray in 3 fractions by using volumetric arc therapy concurrently with capecitabine 625mg/m² daily. A magnetic resonance imaging scan of pelvis with contrast was done at 5-10 weeks before surgery. Histological response to neoadjuvant treatment of various histological types was evaluated using the Rectal Cancer Regression Grade. Data was analysed using SPSS 22. Results: Of the 182 patients evaluated, 108(59.34%) were included; 64(59.3%) males and 44(40.7%) females. The overall mean age was 45.4±5.2 years. Regression status was grade 1 in 24(22%) patients, grade 2 in 43(40%) and grade 3 in 41(38%) (p=0.074). There were 12(11.11%) patients with signet ring cell, and 10(83.3%) showed pathological tumour regression. There were 17(15.74%) patients with mucinous variant, and 12(70.5%) of had tumour regression. There were 79(73.15%) patients with adenocarcinoma, and 59(74.6%) of them showed tumour regression. . Conclusion: There was less tumour regression in mucinous and signet ring cell variants of adenocarcinoma. Modification and intensification of neoadjuvant therapy may be required in such histologies. Key Words: Chemoradiation, Colorectal cancer, Neoadjuvant, Rectal cancer pathology.